Notes from the Underground - Editors, The (Pomegranate, 2000)
The wheels are also turning which will, probably in the course of the current year, convert The Pomegranate into a peer-reviewed journal. In other words, articles will be submitted to a panel of reviewers for evaluation. These reviewers will independently decide whether to accept the piece as it stands or to recommend to the editorsthat it be revised according to their suggestions.